Homoclinic and big bang bifurcations of an embedding of 1D Allee's functions into a 2D diffeomorphism - Rocha, J. Leonel (2019)
In this work a thorough study is presented of the bifurcation structure of an embedding of one-dimensional Allee's functions into a two-dimensional diffeomorphism. A complete classification of the nature and stability of the fixed points, on the contour lines of the two-dimensional diffeomorphism, is provided. A necessary and sufficient condition so that the Allee fixed point is a snapback repeller is established. Sufficient conditions for the occurrence of homoclinic tangencies of a saddle fixed point of the two-dimensional diffeomorphism are also established, associated to the snapback repeller bifurcation of the endomorphism defined by the Allee functions. The main results concern homoclinic and big bang bifurcations of the diffeomorphism as "germinal" bifurcations of the Allee functions. Our results confirm previous predictions of structures of homoclinic and big bang bifurcation curves in dimension one and extend these studies to "local" concepts of Allee effect and big bang bifurcations to this two-dimensional exponential diffeomorphism.